Does Mycobacterium bovis persist in cattle in a non-replicative latent state as Mycobacterium tuberculosis in human beings? - Sabio Y Garcia, Julia Veronica; Bigi, María Mercedes; Klepp, Laura Ines; Garcia, Elizabeth Andrea; Blanco, Federico Carlos; Bigi, Fabiana (Elsevier, 2020)
Members of the Mycobacterium tuberculosis complex (MTBC) are responsible for tuberculosis in several mammals. In this complex, Mycobacterium tuberculosis and Mycobacterium bovis, which are closely related, show host preference for humans and cattle, respectively. Although human and bovine tuberculosis are clinically similar, M. tuberculosis mostly causes latent infection in humans, whereas M. bovis frequently leads to an acute infection in cattle. This review attempts to connect the pathology in experimental animal models as well as the cellular responses to M. bovis and M. tuberculosis regarding the differences in protein expression and regulatory mechanisms of both pathogens that could explain their apparent divergent latency behaviour. The occurrence of latent bovine tuberculosis (bTB) would represent a serious complication for the eradication of the disease in cattle, with the risk of onward transmission to humans. Thus, understanding the physiological events that may lead to the state of latency in bTB could assist in the development of appropriate prevention and control tools.